Consort 2010 statement: extension to cluster randomised trials. (4th September 2012) - Campbell, Marion K; Piaggio, Gilda; Elbourne, Diana R; Altman, Douglas G
Abstract : The Consolidated Standards of Reporting Trials (CONSORT) statement was developed to improve the reporting of randomised controlled trials. It was initially published in 1996 and focused on the reporting of parallel group randomised controlled trials. The statement was revised in 2001, with a further update in 2010. A separate CONSORT statement for the reporting of abstracts was published in 2008. In earlier papers we considered the implications of the 2001 version of the CONSORT statement for the reporting of cluster randomised trial. In this paper we provide updated and extended guidance, based on the 2010 version of the CONSORT statement and the 2008 CONSORT statement for the reporting of abstracts.